Preparation and Characterization of Long Alkyl Chain Methacrylate-Based Monolithic Column for Capillary Chromatography in Separation of Alkylbenzene Compound - Rahmah, Athika; Mairizki, Fitri; Putri, Radhia; Zein, Rahmiana; Munaf, Edison; Takeuchi, Toyohide; Wah Lim, Lee (Asian Journal of Chemistry, 2014)
This research describes preparation and characterization of long alkyl chain methacrylate-base monolith for using as stationary phase in capillary liquid chromatography. Preparation of monolithic column were used dodecylmethacrylate as monomer, ethylene dimethacrylate as crosslinker and used a binary porogenic solvent consist of 1.4-butanediol and other 4 various porogen: ethanol, 1-propanol, isoamyl alcohol and isobutyl alcohol. The monolith column were prepared in 100 × 0.32 mm i.d. capillaries column and were optimized in effect of various mobile phase and effect of concentration of mobile phase for separation alkyl benzene compound. Morphology of monolithic column were characterized using scanning electron microscopy. Permeability of column (Ko) was measured by pumping water through to the column with different linear flow rate. The resulting monolithic column with 1.4-butanediol and 1-propanol as porogen have good performed in separation of alkyl benzene compound with acetonitrile-water (80:20) as mobile phase.